Assessment of selected factors and work stress among civil servants in Oyo State, Nigeria (2022)
This study investigates selected factors on work stress among civil servants in Oyo state. The study adopted a descriptive research design of correlation type. A total of 549 civil servants in Oyo state were selected using stratified random sampling technique. Questionnaires consisting of demographic information and sections which are standardized scales on work stress, locus of control, emotional intelligence and self-efficacy were used for this study. The reliability of the scales are; work stress α =.73, locus of control α =.70, emotional intelligence α =.750 and self-efficacy α =.79 Three research questions were raised and answered using Pearson Product Moment Correlation and Multiple Regression Analysis. The findings showed that locus of control (r =.870, p<0.05), emotional intelligence (r =.859, p<0.05), self-efficacy (r =.763, p<0.05), gender (r =.447, p<0.05) and family background (r =.313, p<0.05) had significant relationship to work stress among civil servants in Oyo state. All independent variables jointly accounted for 80.1% variance in predicting work stress of civil servants in Oyo state. Also, locus of control (β = .507, p<0.05), emotional intelligence (β = .341, p<0.05) and gender (β = .124, p<0.05) had significant relative influence to work stress while self-efficacy (β = .075, p>.0.05) and family background (β = .052, p < 0.05) had no significant relative influence to work stress of civil servants in Oyo state. Conclusion was made that the selected factors are actually determined the work stress among civil servants in Oyo state.